Pemanfaatan Sistem Informasi Geografi dalam Pengembangan Pariwisata - Riwayatiningsih Riwayatiningsih; Hartuti Purnaweni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Tourism is a prime sector that is one of the most important factors in the region development and the communitywelfare improvement in a country, which has continuous expansion and diversification and become one of thelargest growth sectors in the world. Increased tourism destinations make the tourism as a key factor in revenue,job creation, business and infrastructure development so that required more advanced planning. This tourismplanning is not intended to damage the environment but it must be planned and implemented to the environmentthat supports the sustainable development. One of the technologies used in some tourism research is GeographicInformation System (GIS) technology. Utilizing GIS technology is expected to be able to analyze the spatialaspects of an area so the existing of tourism potencies can be developed into an optimal object and touristattraction that can attract tourists both domestic and foreign. The aim of this article is to determine the benefitsof Geographic Information System technology in tourism development based on literature studies of previousstudies.